Theories of physical activity behaviour change: A history and synthesis of approaches. (May 2019) - Rhodes, Ryan E.; McEwan, Desmond; Rebar, Amanda L.
Abstract: Background: Most people in developed countries are not physically active enough to reap optimal health benefits so effective promotion strategies are warranted. Theories of behaviour change are essential to understand physical activity and provide an organizing framework for effective intervention. The purpose of this paper was to provide a narrative historical overview of four key theoretical frameworks (social cognitive, humanistic, dual process, socioecological) that have been applied to understand and change physical activity over the last three decades. Methods: Our synthesis of research included the brief history, basic efficacy, strengths, and potential weaknesses of these approaches when applied to physical activity. Results: The dominant framework for understanding physical activity has been in the social cognitive tradition, and it has provided valuable information on key constructs linked to physical activity. The humanistic framework for understanding physical activity has seen a surge in research in the last decade and has demonstrated initial effectiveness in both explaining and intervening on behaviour. The most recent and understudied framework for understanding physical activity is dual process models, which may have promise to provide a broader perspective of motivation by considering non-conscious and hedonic determinants of physical activity. Finally, the individual-level focus of all three of these approaches is contrasted by the socioecological framework, which has seen considerable research attention in the last 15 years and has been instrumental in understanding the role of the built environment in physical activity behaviour and critical to shaping public health policy in government. Conclusions: Despite the strengths of all four frameworks, we noted several weaknesses of each approach at present and highlight several newer applications of integrated models and dynamic models that may serve to improve our understanding and promotion of physical activity over the next decade. Highlights: Provides a narrative historical overview of four key theoretical frameworks applied to understand physical activity over the last three decades. Brief history, basic efficacy, strengths, and potential weaknesses of these approaches are addressed. Highlights applications of integrated and dynamic models that may serve to improve our promotion of physical activity over the next decade.